KURIKULUM MERDEKA: PELUANG DAN TANTANGAN DALAM DINAMIKA PERKEMBANGAN KURIKULUM BERBASIS CINTA DAN MENDALAM (HUMAN-CENTERED EDUCATION) - Ahmad Athoillahy Attaufiqy; Muhammad Khalivi Abqori Mubarok; Muhammad Mizanul Awal; Abdul Bashith (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2026)
The Merdeka Curriculum represents one of Indonesia’s major educational transformations, emphasizing freedom, autonomy, and holistic character development of learners. This study aims to examine the opportunities and challenges in implementing the Merdeka Curriculum through the lens of Human-Centered Education. The research employs a literature review method by analyzing various academic sources, educational policies, and previous studies. The findings reveal that the Merdeka Curriculum offers significant opportunities to strengthen human values, creativity, and learner independence. However, challenges arise regarding teacher readiness, unequal resources, and conceptual understanding of love-based education. Therefore, enhancing teacher competence and strengthening policy collaboration are essential to ensure a deep and sustainable curriculum transformation.